2018
DOI: 10.1111/tpj.13855
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis replication factor C4 is critical for DNA replication during the mitotic cell cycle

Abstract: Replication factor C (RFC) is a conserved eukaryotic complex consisting of RFC1/2/3/4/5. It plays important roles in DNA replication and the cell cycle in yeast and fruit fly. However, it is not very clear how RFC subunits function in higher plants, except for the Arabidopsis (At) subunits AtRFC1 and AtRFC3. In this study, we investigated the functions of AtRFC4 and found that loss of function of AtRFC4 led to an early sporophyte lethality that initiated as early as the elongated zygote stage, all defective em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 106 publications
1
14
0
Order By: Relevance
“…Though no developmental defects were observed in heterozygous plants of the mutants during vegetative growth, their mature siliques contained white abnormal ovules at a frequency of about 25% (Figure 2B ; Table 1 ). All of these results showed that the mutations in AtRFC2/3/5 were lethal in homozygous progenies, similar to the mutant rfc4 (Qian et al, 2018 ).…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…Though no developmental defects were observed in heterozygous plants of the mutants during vegetative growth, their mature siliques contained white abnormal ovules at a frequency of about 25% (Figure 2B ; Table 1 ). All of these results showed that the mutations in AtRFC2/3/5 were lethal in homozygous progenies, similar to the mutant rfc4 (Qian et al, 2018 ).…”
Section: Resultsmentioning
confidence: 72%
“…In Arabidopsis , the expression and function of RFC1 and RFC4 have been reported (Liu et al, 2013 ; Qian et al, 2018 ). To assess the functions of AtRFC2/3/5 , we first detected their expressions in various Arabidopsis tissues using quantitative real-time PCR (qRT-PCR) assays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have shown that AtRFC1 also participates in meiotic homologous recombination [18, 19]. AtRFC3 is involved in negative regulation of systemic acquired resistance, and AtRFC4 is critical for DNA replication during the mitotic cell cycle [20, 21].…”
Section: Introductionmentioning
confidence: 99%